Optimalisasi Pengenalan dan Penggunaan Aplikasi Samarinda Santer dalam meningkatkan Pelayanan Publik di Kota Samarinda - Khaerani, Thalita Rifda; Anggreani , Dinda Aulya; Khairunnisa , Firda (ANDIL Mulawarman Journal of Community Engagement, 2025)
The optimalization of the Samarinda Santer application is part of an effort to enhance digital public services in Samarinda City, specifically in Handil Bakti Village. This jurnal aims to evaluate the effectiveness of the socialization, the challenges encountered, and the social implications of implementing the application. The methods used in the socialization included interactive presentations, application usage simulations, and Q&A sessions, with a focus on community participation. Results indicate an increase in understanding and adoption of the application by the community, although challenges such as varying levels of digital literacy, infrastructure limitations, and resistance to new technology were encountered. The social implications of this socialization include improved accessibility to public services, digital literacy, transparency, and community participation in governance. The paper recommends ongoing technical support, application feature updates, and a more persuasive approach to overcome challenges and enhance technology adoption among the community.